Analysis of the Effectiveness of the Special Allocation Fund (DAK) Drinking Water Program on Drinking Water Access Achievement in Purwakarta Regency - Destiningrum, Natalia; Namara, Idi; Pratiwi, A Andini Radisya (Devotion : Journal of Research and Community Service, 2026)
The Government of Purwakarta Regency seeks to improve access to safe drinking water; however, by 2024, coverage has only reached 64%, still below the 81% target. This study aims to analyze the effectiveness of community-based Drinking Water Supply System (SPAM) management funded through the Special Allocation Fund (DAK) in three villages: Cipicung, Pasirangin, and Pusakamulya. The evaluation refers to five aspects based on Minister of Public Works and Housing Regulation No. 27 of 2016, namely technical, institutional, financial, social, and environmental aspects. The research method combined analysis of existing conditions and stakeholder perceptions. Primary data were collected through surveys and structured interviews with 129 respondents, while secondary data were obtained from relevant regulations. Data analysis employed the Relative Importance Index (RII) and Confidence Interval (CI). The results indicate that water quality is the most influential factor in determining the effectiveness of SPAM management. Cipicung and Pasirangin villages have successfully implemented all aspects, as reflected in good water quality, strong institutional arrangements, and high community participation. Meanwhile, Pusakamulya village faces challenges in the environmental aspect, particularly in water source protection, which affects water availability. The management model applied in Cipicung and Pasirangin can serve as a reference for other areas, with recommendations focusing on infrastructure improvement and strengthening water source protection